Psychiatric conditions as predictors of rehospitalization among African American patients hospitalized with heart failure. Issue 11 (27th July 2017) - Lu, Marvin Louis Roy; De Venecia, Toni Anne; Goyal, Abhinav; Rodriguez Ziccardi, Mary; Kanjanahattakij, Napatt; Shah, Mahek Kishor; Davila, Carlos D.; Figueredo, Vincent M.
Abstract : Introduction: African Americans (AAs) have the highest risk of developing heart failure (HF) among all ethnicities in the United States and are associated with higher rates of readmissions and mortality. This study aims to determine the prevalence and relationship of common psychiatric conditions to outcomes of patients hospitalized with HF. Hypothesis: Psychiatric conditions lead to worse outcomes in HF patients. Methods: This single‐center retrospective study enrolled 611 AA patients admitted to an urban teaching community hospital for HF from 2010 to 2013. Patient demographics, clinical variables, and history of psychiatric disorders were obtained. Cox proportional hazards regression was used to assess impact of psychiatric disorders on readmission rates and mortality. Results: The mean age was 66 ± 15 years; 53% were men. Median follow‐up time from index admission for HF was 3.2 years. Ninety‐seven patients had a psychiatric condition: 46 had depression, 11 had bipolar mood disorder (BMD), and 40 had schizophrenia. After adjustment of known risk factors and clinical metrics, our study showed that AA HF patients with a psychiatric illness were 3.84× more likely to be admitted within 30 days for HF, compared with those without ( P  < 0.001). Individually, adjusted Cox multivariable logistic regression analysis also showed that, for 30‐day readmission, schizophrenia had a hazard ratio (HR) of 4.92 ( P  < 0.001); BMD, an HR of 3.44 ( P  = 0.02); and depression, an HR 3.15 ( P  = 0.001). No associations were found with mortality. Conclusions: Psychiatric conditions of schizophrenia, BMD, and depression were significantly associated with a higher 30‐day and overall readmission rate for HF among AA patients.